Investigating the Climate Change, Natural Disasters and Tourism Industry in Himachal Pradesh, India - Singh, Gajendra; Bangia, Gayatri; Chauhan, Satyendra Singh (Indonesia Academia Research Society, 2024)
Tourism is a major global economic sector undergoing tremendous growth in emerging economies and is often touted as salient for development and poverty alleviation in developing countries. Tourism is recognized as a highly climate-sensitive sector, one that is also strongly influenced by environmental and socioeconomic change influenced by climate change. This research examines climate changes and natural disasters' ramifications on tourism businesses in Himachal Pradesh, India. It encompasses factors such as supply chain interruptions, distribution network inefficiencies, and trade blockades affecting market demand, tourist influx, information technology issues, and the necessity for risk management in changing climatic conditions. Additionally, the demographic profiles of 500 respondents are analyzed to understand the specific challenges tourism businesses face. The findings of this research contribute to the understanding of the complex interplay between climate change, natural disasters, and tourism in Himachal Pradesh. They serve as a foundational framework for formulating strategies geared toward augmenting the resilience and sustainability of tourism enterprises when confronted with these challenges, ultimately ensuring the enduring prosperity of regions heavily reliant on tourism.